The Impact of Corruption on Economic Growth in Malaysia - Yusof, Muhammad Hafizuddin; Jit, Keshminder; Ridzuan, Abdul Rahim (Advances in Social Sciences Research Journal, 2023)
The impact of corruption on economic growth has been the subject of theoretical debate among economists, with some arguing that corruption hinders growth and development. In contrast, others suggest that it can positively affect the development process. As such, the effects of corruption on economic growth remain inconclusive. This study examines corruption's impact on economic growth, as measured by real GDP per capita (constant 2015 US$) in Malaysia. The study utilized the autoregressive distributed lag (ARDL) method to investigate the relationship between corruption and economic growth in Malaysia. The data used in the analysis were obtained from the World Bank and International Country Risk Guide data repository and covered the period of 1992-2021 annually. The Corruption Index was used to measure corruption. At the same time, other variables included economic growth (GDP), Gross Capital Formation (GCF), General Government Final Consumption Expenditure (GE), Individuals Using the Internet (INT), Labor Force (LF), and School Enrollment (SE) in Malaysia. The study's primary results are as follows: (1) corruption and economic growth in Malaysia have a long run relationship when considering the measures of GCF, GE, INT, LF, and SE in the model; (2) when the measures of GCF, GE, INT, LF, and SE were included interchangeably and combined in the model, corruption had a positive and significant impact on economic growth in Malaysia; (3) corruption and economic growth in Malaysia have a significant short-run relationship when considering the measures of GCF, GE, INT, LF, and SE in the model. The study's limitation relates to the data used, as alternative corruption measures beyond the corruption index could yield different outcomes. The study's distinctive contribution is exploring the impact and relationship between corruption and economic growth, specifically in Malaysia.